Organic practices and gender are effective strategies to provide healthy pork loin - Javier Álvarez-Rodríguez; Daniel Villalba; Dolors Cubiló; Daniel Babot; Marc Tor (Journal of Integrative Agriculture, 2016)
This study evaluated the influence of husbandry (organic feed and management but not free-ranging vs. conventional) and sex (barrows vs. gilts) on pork meat quality. A total of 60 Longissimus thoracis pork muscle samples from different 3-way crossbred genotypes were chosen from 3 conventional and 2 organic pig farms. Technological meat quality was measured at 24 h post-mortem and muscle fatty acid content and composition was analysed by gas chromatography. The loin from organic pigs at 24 h of retail display had lower pH, but it had no detrimental effects on drip loss. All the International Commission on Illumination colour attributes except meat lightness differed between husbandry systems. Moisture and crude protein content were lower whereas intramuscular fat content was greater in organic than in conventional pork. Total saturated fatty acid (SFA), monounsaturated fatty acid (MUFA), polyunsaturated fatty acid (PUFA) and PUFA n-6 contents did not differ between husbandry systems, but total PUFA n-3 (mainly C18:3 n-3) were greater in organic than in conventional pork. Sex did not affect ultimate pH or meat colour attributes but barrows showed lower moisture and greater intramuscular fat than gilts. Total SFA and MUFA content were similar but all the PUFA (both n-6 and n-3) were lower in barrows than in gilts. These results suggest that some bioactive compounds from dietary origin, i.e., linolenic acid (C18:3 n-3) content from dietary vegetable oils (soybean or olive olein), might be used to highlight the nutritive value of (not free-ranging) organic pork meat. In addition, gilts were leaner than barrows and showed a more favourable PUFA/SFA ratio.